The enhancement of talent in companies, between innovation of organizational forms of work and learning models - Richini, Pierluigi (Formazione & insegnamento, 2018)
The present contribution takes into consideration a specific aspect of learning in the workplace, with regard to the close interaction between skills development, talent valorisation, flexibility of organizational forms and methods of work governance. The transformations taking place in the productive world require a different consideration of management practices for which, at present, the preconditions are recognized, together with several experiences of revision of the forms of work organization. This implies an overall review of the business strategies, with particular reference to the models of human resources development, able to take into account the new complexities that the transformation poses, not only in terms of production practices but also new social issues and the new relationship between human prerogatives and technology.